Antifungal peptides from living organisms - Gong, Yi; Xue, Qunhang; Li, Jun; Zhang, Shicui (Frontiers in Microbiology, 2024)
In the post-COVID-19 era, people are increasingly concerned about microbial infections, including fungal infections that have risen in recent years. However, the currently available antifungal agents are rather limited. Worse still, the widespread use of the antifungal agents has caused the emergence of antifungal resistance in Candida, Cryptococcus, and Aspergillus species. Therefore, the development of novel antifungals is urgently needed. Antimicrobial peptides (AMPs), as components of the first-line defense of the host, are found to exhibit broad antimicrobial activity against bacteria, fungi, parasites, viruses, and protozoa. AMPs with antifungal activity are specifically referred to as antifungal peptides (AFPs). AFPs are currently regarded as the most promising alternative to conventional antifungal agents due to the fact that they are highly selective and less prone to facilitate the selection of drug resistance. In this review, we present an overview of the origin and classification of natural AFPs as well as their modes of action. Additionally, the production of natural, semisynthetic, and synthetic AFPs with a view to greater levels of exploitation is discussed. Finally, we evaluate the current and potential applications of AFPs in clinics and in the food industry.